Perencanaan Komunikasi Program Studi Komunikasi dan Penyiaran Islam Universitas Islam Negeri Raden Fatah Palembang - Fifi Hasmawati; Eva Nuryanti (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2019)
Communication is a process, of which a person, a group, society or community, that use information as connection among environment and others. Management is mostly defined as an art for working implementation through others. Therefore management communication is a coherent between concept of communication and management, which implemented in varies of communication activities, with purposes to make it effectively implemented. Therefore every expected message or out coming based on delivery will be achieved. Management communication itself consists of two word. Which is: management and information. During the process, management works thru it functions, which is planning, organizing, controlling, and leading every effort achieving goals.